As nuances da civilização: consumo e cotidiano na fronteira meridional do Brasil, Alegrete (1846 – 1891) - Tomazi, Taís Giacomini (2018)
This research has as its theme the study of the consumption of long, medium and perishable goods in a frontier region in the 19th century. The objective was to investigate the characteristics of consumption on the southern border of the Empire of Brazil, focusing on the city of Alegrete in the second half of the century (1846-1891), as well as searching for clues about daily life and new conceptions of civilization and social life. The sources used were Postmortem Inventories of Alegrete (Public Archive of the State of Rio Grande do Sul), analyzed every 5 years within the historical period of the research, with serial history as the main methodological contribution. Reports of Travelers, Gazeta de Alegrete (Public Archive of the State of Rio Grande do Sul) and Code of Municipal Postures (Historical Archive of Rio Grande do Sul) are other sources that composed the investigation and had as methodological support a qualitative reading relating such sources with context and historiography. The results indicate that there was a trend of consumption related to goods of greater daily use, there were also some changes in the consumption of some typologies of these goods more at the end of the nineteenth century and even the cheapening of some of them and perhaps greater access. In turn, an analysis of the goods from socio-economic groups ended up demonstrating the existence of an average urban space for the region, even though it was totally connected to the rural universe, which was predominant in that context. It was also noticed that the wealthiest groups had the highest amounts of goods in all categories, but average groups ended up having more goods than other goods of production, which is accentuated in relation to the poorest indicating the stratification in the region. Still, it is possible to say that the durable and perishable goods indicated an interesting commercial movement and of consumption, with products of varied types. The municipality was still supported in diverse stores and commercial activities that brought to the region the innovations of the European Atlantic world and platino. And finally, it was noticed that new products were inserted in the daily life and ended up being part of the consumption of many people of the region, but we consider that despite the insertion of these new elements and even of conceptions of European "civility", there was not a cultural overlap but rather an interaction of these aspects, bringing together the already established daily practices with the innovations from beyond the sea.